Language, power and identity politics - Nic Craith, Máiréad (Palgrave studies in minority languages and communities., 2007)
The contributors to this book explore the significance of language in articulating and maintaining identity in the context of power relations at all levels in society. As globalization gains momentum, and new technologies emerge, concepts of power and information are reshaped and the role of language changes. Contributions examine the importance of English as an indicator of power and influence in global contexts. The authors also focus on the new transnational context for minority language activists within the EU. Such benefits have not been extended to speakers of immigrant languages as the principle of indigeneity continues to remain central to language policy. Different mother tongues divide migrant and indigenous populations but relations can be vastly improved with structures reinforcing intercultural communication. Language can also act as boundary between peoples of different faiths and ethnic backgrounds and the final contribution explores changing concepts in the wake of 9/11 and the subsequent 'war on terror'.